(untitled) (American International Journal of Economics and Finance Research, 2019)
This paper investigated the impact of information and communication technology on the Nigerian economy, taking evidence from the banking sector. Ordinary least squares method of regression for the period 2004-2017 was employed. Generally, the paper found that there was positive relationship between bank related information and communication technology components used and economic growth, except the automated teller machine component, under a fixed effect modeling. However, using the Breusch Godfrey (BG) dynamic modeling to remove serial autocorrelation, the paper revealed that only the mobile banking payment component positively and significantly affected the gross domestic product. On the basis of the findings, the researcher recommended that the Central Bank of Nigeria, banks and stakeholders should collaborate to strengthen the information and communication infrastructures and security systems in the country to reduce frauds, make the environment user friendly and improve public confidence.